2022
DOI: 10.3390/ph15050625
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy Approach for Highly-Efficient Screening of Lectin-Ligand Interactions in Application for Mannose Receptor and Molecular Containers for Antibacterial Drugs

Abstract: Rational search of a ligand for a specific receptor is a cornerstone of a typical drug discovery process. However, to make it more “rational” one would appreciate having detailed information on the functional groups involved in ligand-receptor interaction. Typically, the 3D structure of a ligand-receptor complex can be built on the basis of time-consuming X-ray crystallography data. Here, a combination of FTIR and fluorescence methods, together with appropriate processing, yields valuable information about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(70 citation statements)
references
References 84 publications
2
45
1
Order By: Relevance
“…This can be explained by the possibility of apiol interacting with the outer hydrophilic shell of the CD (in addition to the CD cavity itself), which is less typical for EG, which forms an order of magnitude stronger guest–host inclusion complex. Moreover, this phenomenon depends on the amount of CD added, as we have previously demonstrated by the interaction of EG with mannosylated polymer and molecular containers [ 29 ]. Nuchuchua et al [ 22 ] have also observed a decrease in the intensity of the EG peak in the solid-phase EG–CD spectra.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This can be explained by the possibility of apiol interacting with the outer hydrophilic shell of the CD (in addition to the CD cavity itself), which is less typical for EG, which forms an order of magnitude stronger guest–host inclusion complex. Moreover, this phenomenon depends on the amount of CD added, as we have previously demonstrated by the interaction of EG with mannosylated polymer and molecular containers [ 29 ]. Nuchuchua et al [ 22 ] have also observed a decrease in the intensity of the EG peak in the solid-phase EG–CD spectra.…”
Section: Resultsmentioning
confidence: 78%
“…ATR-FTIR spectra of solid samples placed on KBr glass were recorded using a Bruker Lumos II IR microscope in the region from 700 to 4000 cm −1 with 1 cm −1 spectral resolution with scanning in the area on average 1 × 1 microns. Spectral data were processed using the Bruker software system Opus 8.2.28 (Bruker, Germany), which includes linear blank subtraction, baseline correction, differentiation (second order, 17–21 smoothing points), min–max normalization and atmosphere compensation [ 29 , 56 ]. If necessary, 5-point Savitsky–Golay smoothing was used to remove noise.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, a significant potential of allylbenzenes, including eugenol (EG), and terpenoids, which are synergists of fluoroquinolones, has been demonstrated [ 10 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. As promising adjuvants, apiol and its analogs dillapiole, myristicin, and nothoapiol should be noted [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD206 is a C-type lectin (175 kDa), which is a transmembrane protein that binds carbohydrates due to a lectin-like region of eight domains [ 39 , 42 ]. However, since CD206 itself is difficult to isolate, model receptor proteins, for example, concanavalin A (ConA), are often used to screen the affinity of mannosylated delivery systems to macrophage mannose receptors [ 25 , 43 , 44 , 45 , 46 , 47 , 48 ]. The relevance of the ConA model was previously demonstrated using molecular dynamics and neural network analysis [ 43 ] as well as in vivo and in vitro experiments, which demonstrated that highly ConA-specific delivery systems effectively target macrophages [ 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation